ENSURING MACROECONOMIC STABILITY BY IMPLEMENTING STRUCTURAL REFORMS IN THE ECONOMY - Khakimova , Saodat (Educational Research in Universal Sciences, 2023)
This article aims to analyze the impact and effectiveness of implementing structural reforms as a means of ensuring macroeconomic stability in modern economies. The study examines the relevant economic literature, case studies, and the theoretical underpinnings of structural reforms and their relationship to macroeconomic stability.